PENGARUH KECERDASAN LINGUISTIK TERHADAP KEMAMPUAN KONEKSI MATEMATIS DALAM MENYELESAIKAN MASALAH OPEN ENDED MATERI TRIGONOMETRI - Fitriani, Ulliya; Aunur Rohman, Ahmad; Cahyono, Budi (Sains and Technology Faculty, Walisongo State Islamic University, 2018)
This study aims to determine the effect of linguistic intelligence on students mathematical connection ability in solving open-ended problems on the trigonometric material. Linguistic intelligence is the ability to use and process words effectively both verbally and in writing with appropriate or appropriate meaning. The ability of mathematical connections is the ability to associate mathematical concepts between mathematical concepts, linking mathematical concepts with other fields of science and linking mathematical concepts with everyday life. Students who have mathematical connection skills can solve life problems or challenges faced by connecting mathematical concepts. Mathematical connection ability requires linguistic intelligence which refers to Howard Gardners opinion to solve open-ended problems that have more than one solution. This research is a quantitative research involving 116 students. The research was carried out by survey method and data analysis method using simple linear regression analysis. While data collection is done by questionnaire and test. Based on the results of the study formed a simple linear regression equation Å¶ = 21.26 + 0.62X, which means that linguistic intelligence influences the ability of students mathematical connections in solving open-ended problems and gives an effect of 38.13%. Thus, linguistic intelligence has a significant influence on the ability of mathematical connections of Walisongo UIN mathematics students in solving open-ended trigonometric material problems.